Spontaneous laceration of spleen with hilar lymph node metastasis: a case of primary splenic mantle cell lymphoma in elderly - Bhargav, Mithlesh; Mehrotra, Bandana; Kapoor, Ashok; Raj Gopal, Vaibhav (International Journal of Research in Medical Sciences, 2024)
Mantle cell lymphoma (MCL) is a type of non-Hodgkin (B-cell) lymphoma (NHL) with manifestations ranging from indolent to aggressive disease. It arises from mantle zone or primary follicle lymphocytes and is associated with translocation t (11;14) which is seen in almost all cases. Most of the cases present at stage III/IV with hepatospenomegaly, generalized lymphadenopathy, bone marrow involvement or lymphoid polyposis. Rate of relapse is high occurring in 50-60% patients and 5-year survival rates are low ~27-30%. Median overall survival is 3.5 years. Age >60 years, raised serum LDH, high mitotic count, Ki67>30%, blastoid or pleomorphic variants, TP53 mutation, gains in 3q,11q and deletions of 13q as well as 17p are important prognostic factors associated with worst outcome. Treatment involves conventional chemo-immunotherapy and stem cell transplantation (SCT). In our case the elderly patient had an atraumatic splenic rupture with no past medical history of trauma. The patient presented to the emergency department with severe abdominal pain in left upper quadrant. Thus emergency splenectomy was executed successfully, and the patient was stabilized. After receiving initial cycle of R-CHOP regime, he was lost to follow up. In this case report, we will discuss the clinical presentation, as well as current treatment guidelines for atraumatic splenic rupture.